The People's Festival enlivens UMPSA's ‘Kembara Prihatin’ solicitude for the indigenous community - Nur Hartini, Mohd Hatta (UMPSA, 2024)
CAMERON HIGHLANDS, 27 July 2024 - Over 500 people attended the People's Festival and communal work programme in conjunction wi’th Kembara Prihatin’@Pos Telanok, bringing the expertise and technology of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) to the indigenous community in Cameron Highlands.